Exploring the Nexus of Holography and Holophony in Visual Music Composition. - Rhoades, Michael (Leonardo Music Journal, 2020)
In this article the author explores the idea that, owing to their shared three-dimensional nature, holophons and virtual holograms are well suited as mediums for visual music composition. This union is ripe with creative opportunity and fraught with challenges in the areas of aesthetics and technical implementation. Squarely situated upon the bleeding edge of phenomenological research and creative practice, this novel medium is within reach. Here, one methodological pipeline is delineated that employs the convergence of holophony, virtual holography and supercomputing toward the creation of visual music compositions intended for head-mounted displays or large-scale 3D/360-degree projection screens and high-density loudspeaker arrays.